Effects of machining characteristics on electric discharge machine using different electrode materials - Mohd Khairul Anuar, Mohd Idris (2008)
Electric discharge machining (EDM) is a non-traditional machining processes that involved a transient spark discharges through the fluid due to the potential difference between the electrode and the work piece. The aim of this project is to determine the proper electrode material for machining tool steels work pieces using electrical discharge machining (EDM). Basically, improper choose of electrode material in EDM machine may result a few problems like the machine may cause of poor machining performance and it will decrease the accuracy of the products. This paper presents a fundamental study of characteristic of electrode discharge machine (EDM) that is electrode wear ratio (EWR) and material removal rate (MRR) by using different electrode materials in order to increase the understanding of EDM processes. To archive this project objective, an experiment will be doing properly. By following the method, some literature review is going to do first before preparing the experimental set-up. Then experiment will be runs and the data of the experiment are taken. This is to make sure the analysis can be done in order to find the best electrode material. There are three electrodes material should be compared that are copper, brass and aluminum. Regarding the literature review, the higher material removal rate in the EDM machine, the better is the machining performance while the lower electrodes wear ratio in the EDM machine is the better and accurate performance characteristic. Thus as the expected result for this experiment, the copper electrode material will be the best electrode among others electrode for EDM machining process.